Analysis of Supply Chain Management Implementation on Amazon E-Commerce - Murni Sofiah; Siti Aisyah (Journal of Indonesian Management, 2022)
Supply chain management itself provides a concept or mechanism that can increase the overall productivity of the company in the supply flow by optimizing the time, location, and flow of material quantities. Because one of the supply chain systems in question today is Amazon's e-commerce company, the purpose of this study is to find the implementation of a supply chain management system on Amazon's e-commerce. This research method uses a qualitative descriptive method by using relevant narratives from various trusted sources through websites or search. There are around 100 populations of E-commerce companies around the world in the 90s to 2022 with a total sample of 1 sample, namely the Amazon E-commerce company. The results show that Amazon has forced its competitors to increase aspects of supply chain automation, shorten delivery times, increase the number of warehouses, and engage in product manufacturing. With a combination of advanced information technology, extensive warehousing networks, multi-level inventory management, and reliable transportation, Amazon's supply chain is the world's most efficient leading company. There are six supply chain management applicable to Amazon e-commerce companies, namely- Outsourcing Inventory Management and Insourcing Logistics, Delivery Options To Customers, Push/Pull Strategy for Supply chain Success, Amazon's Warehouse Classes and Zones, Warehouse Automation and Supply Chain Cost.